The effect of surface treatment on composite interface, tensile properties and water absorption of suger palm fiber/polypropylene composites - Wan Zahari, Wan Zubaidie (2017)
The rising concern towards environmental issues besides the requirement for more flexible polymer-based material has led to increasing of interest in studying about green composite. Sugar palm fiber (SPF) is a versatile fiber plant employed with wide range of application such as in automotive, packaging and buildings construction. This research was aimed to study the effect of surface treatment on composite interface, tensile properties and water absorption of sugar palm fiber/polypropylene (SPFPP) composite by using different surface treatments such as silane (Si), atmospheric glow discharge plasma (Agd) and maleic anhydride (Ma). Silane treatment was carried out by using immersion method, the Agd plasma was conducted using polymerization and lastly polypropylene grafted maleic anhydride by using melting approach. The SPFPP composite was prepared by using injection moulding with fiber content varied from 10-30wt%. The effect of interface enhancement on morphology, mechanical properties and water uptakes of SPFPP composites were then investigated by using FfIR, FESEM, tensile test and water absorption test. Overall, the outcome shows that aJl types of surface treatments had improved the interface of SPFPP composite, thus improving its tensile properties compared to the benchmark untreated SPFPP (UtSPFPP) composites and polypropylene. The 30wt% Ma-SPFPP composite shows the highest improvement in tensile properties with 58% and 27% increase in the respective Young's Modulus and tensile strength value compared to Ut-SPFPP composite, while 10wt% Ma-SPFPP composite shows the smallest reduction in elongation compared to Neat PP. On the other hand, the 30wt% Si-SPFPP composite shows the lowest water absorption with 20% reduction respective to Ut-SPFPP composite. In conclusion, the surface treatments have proven succesfull in enhancing the natural fiber-polymer interface and improve the tensile properties of SPFPP composite with Ma-SPFPP shows the highest improvement, foJlowed by Agd-SPFPP and Si-SPFPP composites.